عناصر القاعدة الشرعية: Components of Shari’ah Rule - Sabah Muhammad al-Barzanji - البرزنجي, صباح محمـد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2018)
يتناول هذا البحث مصطلح "القاعدة الشرعية" بوصفه مرادفاً للقاعدة القانونية، على أساس أن القاعدة القانونية تُمثِّل قاعدة عامة مجردة، غايتها تنظيم الحياة الاجتماعية بأبعادها المختلفة، وكذا القاعدة الشرعية التي تتحرّى الغاية نفسها، مع وجود فارقين جوهريين؛ أولهما أن القاعدة القانونية هي وضع بشري خاص يتم بإجراءات تشريعية محدَّدة، والقاعدة الشرعية هي نص من الوحي، أو استنباط من الوحي، وثانيهما أن القاعدة القانونية تختص بعلاقات الناس ومعاملاتهم العملية، والقاعدة الشرعية تضيف إلى ذلك علاقة الإنسان بربه. والقاعدة الشرعية قضيةٌ كليةٌ تنطبق على جزئياتها، أو مفهوم كلي ينطبق على أفراده. وكل قاعدة شرعية تتضمَّن ثلاثة عناصر: الفرضية، والحكم، والنسبة الواقعية بينهما، وتتصف بالعقلانية والانسجام مع الفطرة السليمة. This paper deals with the term Islamic Shari'ah rule as synonymous with legal rule. The legal rule is a general and abstract rule with the purpose of regulating the social life in its diverse dimensions. The Islamic Shari'ah rule has the same purpose, with two fundamental differences. Firstly the legal rule is a special human decision that is carried out by specific legislative procedures while the Shari'ah rule is a text of revelation or deduction from revelation. Secondly, the legal rule is concerned with the relations among people and their practical transactions, while the Shari'ah rule adds to that the relationship between people and their God. The Shari'ah rule is a general case that applies to its specifics, or a holistic concept that applies to its elements. Each Shari’ah rule has three components: hypothesis, judgment, and real relation between them. This rule is characterized by rationality and harmony with natural extent, fitra.